Real and simulated altitude training and performance - Hamlin, M. J.; Draper. N.; Hellemans, J. (Current Issues in Sports and Exercise Medicine, 2013)
The use of altitude training to compliment normal training at sea level is widely used by coaches and athletes. There are a number of different altitude training models which range from living and training at moderate and high altitude to breathing hypoxic gas while living and training normally at sea level. In this chapter we will briefly overview the history of altitude training and touch on the science and practice of the various models of altitude training. We also discuss the beneficial effects reported in the scientific literature and give first-hand accounts of the effectiveness of the various methods from high performance coaches. Benefits and drawbacks from each altitude method will be discussed along with advice on preparing athletes prior to altitude training.